Music in Medieval & Early Modern Europe: Patronage, Sources and Texts - Fenlon, Iain (Cambridge Cambridge University Press, 1981)
This volume consists of original papers first read at King's College, Cambridge, in 1979 at an international conference on medieval and Renaissance music. The contributors are distinguished in a wide variety of musicological interests but all are concerned in one way or another with pursuing the most urgent and promising directions for research in early music history. The result, far from being merely a further collection of essays applying well-tried approaches to familiar material, constantly seeks to expand the scope of musicology itself, and many of the contributions arc inter-disciplinary in method. The four main topics of the conference were carefully chosen, with some editorial control exercised for each session. This is reflected in four sections of closely related papers in the book. Two of these are concerned with the patronage of music: by the Church in fifteenth-century England, Italy and France, and in a broader context in Italy from 1450 to 1550. A group of essays on sixteenth-century instrumental music separates these, and the book concludes with five papers on theories of filiation as applied to music sources from the tenth to the sixteenth century.
Keywords: Middle Ages (500-1400); Renaissance (1400-1600); Music history; Patronage; Europe